Counterfactuals in Context: Felicity conditions for counterfactual conditionals containing proper names - Robinson, William Stephen (My University, 2013)
This thesis provides felicity conditions for counterfactual conditionals containing proper names in which essential changes to an individual are counterfactually posited using contrastive focus in either the antecedent or consequent clause. The felicity conditions proposed are an adaptation of Heim's (1992) CCP Semantics into Kratzer's (1981) truth conditions for counterfactual conditionals in which the partition function f(w) serves as the local context of evaluation for the antecedent clause, while the set of worlds characterized by the antecedent serves as the local context for the consequent clause. In order for the felicity conditions to generate the right results, it is shown that they must be couched in a rigid designator/essentialist framework inspired by Kripke (1980). This correctly predicts that consequents containing rigid designators are infelicitous when their input context--the set of worlds accessible from the antecedent clause--does not contain a suitable referent.
Thesis (Master's)--University of Washington, 2013
Keywords: conditional; context change; counterfactual; Kripke; presupposition; rigid designator; Linguistics; Philosophy; linguistics